About the effect of eye blinking on drug release from pHEMA-based hydrogels: an in vitro study - Galante, Raquel (2015)
"The development of new ophthalmic drug delivery systems capable of increasing the residence time of drugs in the eye and improve its bioavailability relatively to eyedrops has been object of intense research in recent years. Several studies have shown that drug loaded therapeutic soft contact lenses (SCLs) constitute a promising approach, with several potential advantages as compared with collyria. The main objective of this work is to study the effect of repetitive load and friction cycles caused by the eye blinking, on the drug release from hydrogels used in SCLs which, as far as we know, was never investigated before. Two poly-2-hydroxyethylmethacrylate based hydrogels, pHEMA-T and pHEMA-UV, were used as model materials. Levofloxaxin was chosen as model drug. The hydrogels were fully characterized in what concerns structural and physicochemical properties. PHEMA-UV revealed some superficial porosity and a lower short range order than PHEMA-T. We observe that the load and friction cycles enhanced the drug release from pHEMAUV hydrogels. The application of a simple mathematical model, which takes into account the drug dilution caused by the tear flow, showed that the enhancement of the drug release caused by blinking on this hydrogel may be relevant in in vivo conditions. Conversely, the more sustained drug release from pHEMA-T is not affected by load and friction cycles. The conclusion is that, depending on the physicochemical and microstructural characteristics of the hydrogels, blinking is a factor that may affect the amount of drug delivered to the eye by SCLs and should thus be considered."